On the Heresthetics of Salience: Competing over Voters' Attention - Antonella Ianni; Margarita Katsimi; Helia Marreiros (Munich Society for the Promotion of Economic Research - CESifo GmbH, 2025)
This paper investigates a voting model in which two candidates strategically compete in a winner-take-all election. Voters consider both the spatial dimension of policy positions and other attributes, or valence, of each candidate. Candidates are policy motivated and endeavor to make specific attributes "salient" in voters' minds by leveraging their comparative advantages to influence the voting outcome - a form of "heresthetic" behaviour. The paper offers three contributions. First, it characterizes Salient Political Equilibria and suggests ways in which the notion of salience can be made operational. Second, it provides novel experimental evidence supporting voting salient behaviour. Third, it offers empirical evidence that candidates internalize the externality that ensues from voters salient behaviour, in the context of the European migration crisis of 2015. The theoretical, experimental, and empirical findings challenge the conventional median voter paradigm and its implications by highlighting the significant impact of voters' salience on electoral outcomes.
Keywords: D72; D91; 330; voting; salience; valence; heresthetic; experiment